The children of the new forest - Marryat, Frederick; Payal Mittal (New Delhi : Mind Melodies, 2009)
The Children of Colonel Beverley, a Cavalier officer killed at the Battle of Naseby, are believed to have died in the flames when their house is burned by soldiers. However, they escape and are raised by Jacob Armitage, a gamekeeper, in his cottage in the New Forest. The children adapt from an aristocratic lifestyle to that of simple cottagers, who are concealed as the grandchildren of Armitage. After Armitage's death, Edward Beverley leaves and works for the Sympathetic Purtian. He, then, joins the army of the future King Charles II and after the Royalist defeat at the Battle of Worcester, he escapes to France and lives in exile until the Restoration. His siblings continue to live in the New Forest and they are reunited on the King's return.
Keywords: 1642-1649.; England New Forest (Forest).; Fiction